Learning media development of the cheap skin-based model for medical faculty students at Tadulako University - Wisnu Yusron Muhlasin; Fitriah Handayani; Indah Puspasari Kiay Demak; Yuli Fitriana (Research and Development in Education (RaDEn), 2022)
A model is a learning media that is used instead of the real human body to increase students' knowledge and can also practice medical skills, which are impossible to apply to real patients. Learning using models is the first order in learning clinical skills before students proceed to the next stage, namely practicing with friends and the last one is going directly to the community. The purpose of this study was to design, create and analyze a skin model made from cheap raw materials like wood so that it can be used as a learning aid at the Faculty of Medicine, Tadulako University. This research applied a qualitative approach with the Research and Development method. The sampling technique as the informant was taken through purposive sampling. The informants consisted of a dermatologist and sex expert, a medical education expert, and a histology lecturer. Data was collected through in-depth interviews and observation. Data analysis was carried out by analyzing the opinions of the informants using questionnaires to help guide the interview. The cheap leather model shows a fairly realistic mannequin shape with colors that can distinguish each layer and can be used as a learning aid for students in the histology department. Learning media development of the cheap leather model shows a fairly realistic mannequin shape with colors that can distinguish each layer and can be used as a learning aid for students in the histology department.